Factors Affecting Purchase Decision of Life Insurance Policy of Customer in Chitwan - Bista, Manish Bahadur; Upadhyay, Hari Prasad (International Journal of Silkroad Institute of Research and Training, 2023)
Background: Life insurance policy enjoys a unique position in the field of investments and should be judged in this light. The policy owner behaviour towards life insurance than the conventional savings and protection view. The objective of this research was to assess the intentions of people towards purchasing decision of life insurance, to analyze the awareness level of life insurance in Chitwan and to examine the relationship among perception, attitudes, awareness and purchase decision. Methods: An analytical cross-sectional study was conducted among 150 policy holder respondents in Bharatpur, Chitwan, Nepal. Non probability purposive sampling technique was used for data collection. Data was analyzed by using descriptive and inferential statistical tools. In this research Independent Variables was (Purpose of Buying, perception and evaluation alternatives, trust) while dependent Variable was (Purchase of Life Insurance Policy). Data was analysed by using SPSS 20. P-value <0.05 was considered as statistically significant. Results: Majority of the respondents are between 30-40 years age group which is 37.3 percent of the respondents, 26.7 percent of the respondents are 20-30 age groups. Correlation coefficient between the independent variables purpose of buying and dependent variable factor affecting customer purchase life insurance policy is found to be statistically significant. Conclusions: The study concludes that the factors affecting customer purchase on life insurance policy includes education, economic status, medical emergencies, better returns, comparison with other insurance companies, perception of individuals, available alternatives and trust.